2021
DOI: 10.1101/2021.08.25.457624
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-level survey of loss-of-function mutations revealed that background dependent fitness genes are rare and functionally related in yeast

Abstract: In natural populations, the same mutation can lead to different phenotypic outcomes due to the genetic variation that exists among individuals. Such genetic background effects are commonly observed, including in the context of many human diseases. However, systematic characterization of these effects at the species level is still lacking to date. Here, we sought to comprehensively survey background-dependent traits associated with gene loss-of-function (LoF) mutations in 39 natural isolates of Saccharomyces ce… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…These results are reminiscent of the virulence data presented by McCullough et al [ 73 ], who showed, using two batches of the same product, that virulence (defined as growth in the host) may be variable. Such differences in the genetic backgrounds may explain the different outcomes of the iron starvation experiments and the mice infection in this study, detailed below, similarly to how a recent large-scale study showed that variations in S. cerevisiae genetic backgrounds substantially affect gain- or loss-of-fitness effects of loss-of-function mutations [ 74 ].…”
Section: Discussionmentioning
confidence: 75%
“…These results are reminiscent of the virulence data presented by McCullough et al [ 73 ], who showed, using two batches of the same product, that virulence (defined as growth in the host) may be variable. Such differences in the genetic backgrounds may explain the different outcomes of the iron starvation experiments and the mice infection in this study, detailed below, similarly to how a recent large-scale study showed that variations in S. cerevisiae genetic backgrounds substantially affect gain- or loss-of-fitness effects of loss-of-function mutations [ 74 ].…”
Section: Discussionmentioning
confidence: 75%
“…In these cells, despite a strongly deleterious effect on organismal fitness, copies of the mitochondrial genome deleted at loci essential for respiration may outcompete healthy copies thanks to their higher replication origin density (de Zamaroczy et al 1981; Mangin et al 1983; Bernardi 2005). Furthermore, deletion screens in yeasts have also repeatedly identified signals of frequent essentiality switching among genes involved in mitochondrial functions, both across (Kim et al 2010) and within species (Caudal et al 2022; Chen et al 2022), suggesting enhanced evolvability at these loci. In summary, because of unique characteristics and selection pressures, the rate of evolution tends to be higher in the mitochondrial genome than in the nuclear genome, with a critical influence on genetic divergence, speciation, reproductive strategies, and morphology (Hill 2015).…”
Section: Introductionmentioning
confidence: 99%